Differences in enamel surface hardness in soaking carbonated drinks and application of duck eggshell paste remineralization material - Mona, Deli; Hamidah, Izzati; Kurnia, Puji; Abdullah, Khatijah Lim (Universitas Padjadjaran, 2023)
ABSTRACTIntroduction: Demineralization can cause the enamel’s surface hardness to decrease. Carbonated drinks are acidic drinks that can lower the pH of the oral cavity and cause damage to the enamel. Lost tooth minerals can be restored with remineralizing materials, one of which contains calcium. One of the natural materials that can help remineralize is calcium carbonate (CaCO3), which can be found in several animal shells, such as marine materials, pearl snails, and eggshells. Duck eggshell is one of the household wastes that is high in calcium and consists of 94% calcium carbonate. The purpose of this study is to analyze differences in enamel surface hardness in soaking carbonated drinks and the application of duck eggshell paste remineralization material. Methods: This research employed a true experimental laboratory with a pretest-posttest research design with a control group design. The study sample consisted of eight post-extraction premolars that matched the inclusion criteria. The samples were divided into two groups, which were previously soaked in carbonated drinks for 15 minutes. Group I: duck eggshell paste; and Group II: pasta without duck eggshell (control), which was applied for 3 minutes twice a day for 14 days. Hardness measurement using a Vickers hardness tester. Results: Based on data analysis using a paired t-test, enamel surface hardness after immersion in carbonated drinks revealed a mean value of 327.50, SD=23.33. Whereas the enamel surface hardness increased after application of duck eggshell paste (mean=467.50, SD=14.15) p=0.001. The control group also increased after the application of pasta without duck eggshell (mean=429.40 SD=29.01) p=0.002. Conclusion: There is a difference in the hardness of the enamel surface after being soaked in carbonated drinks and after the application of duck eggshell paste. These findings could give potential natural source implications for protecting the teeth.KEYWORDSDemineralization, enamel surface hardness, carbonated drinks, duck eggshell paste, remineralization.